2016
DOI: 10.1177/1557988316664896
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Marijuana Usage and Discrimination Among Adult Black Men

Abstract: Black men may use marijuana as an externalizing coping mechanism to handle the chronic stress of discrimination. The aim of the study was to examine the relationship between everyday and major discrimination and marijuana use among a national sample of Black men. Using the National Survey of American Life, logistic regression analyses was used to determine the association between recent marijuana use and everyday discrimination, major discrimination, and a fully adjusted model that include everyday and major d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…Our findings revealed that male participants who reported higher rates of indirect exposure to perceived racism-based police use-of-force were significantly more likely than females to report cannabis use, which is congruent with previous studies that have found a significant positive association between racial discrimination and cannabis use among Black emerging adult males ( Assari et al, 2019 , Gerrard et al, 2012 , Parker et al, 2017 ). Male participants in the current study may have engaged in cannabis use as a way to cope with their emotional responses to indirect exposure to perceived racism-based police use-of-force events ( Campbell and Valera, 2020 , Gibbons et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings revealed that male participants who reported higher rates of indirect exposure to perceived racism-based police use-of-force were significantly more likely than females to report cannabis use, which is congruent with previous studies that have found a significant positive association between racial discrimination and cannabis use among Black emerging adult males ( Assari et al, 2019 , Gerrard et al, 2012 , Parker et al, 2017 ). Male participants in the current study may have engaged in cannabis use as a way to cope with their emotional responses to indirect exposure to perceived racism-based police use-of-force events ( Campbell and Valera, 2020 , Gibbons et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, this study did not consider measures of psychological functioning. Conversely, Parker et al (2017) did not find an association between everyday discrimination This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 79%
“…This positive association supports previous assertions that disadvantaged neighborhood context can increase minority emerging adult males’ health vulnerability and risk of marijuana use ( Clarke et al, 2014 ; Furr-Holden et al, 2015 ; Green et al, 2016 ; Kogan et al, 2017 ; Powell et al, 2016 ; Stone et al, 2012 ; Uphoff et al, 2013 ). One possible explanation for this relationship is that minority emerging adult males may engage in marijuana use to mitigate their experiences of psychological distress elicited by residing in disadvantaged neighborhoods ( Parker, Benjamin, Archibald, & Thorpe, 2016 ; Preston, 2006 ). The chronic stress of residing in neighborhoods wrought with physical and social problems can lead to depression and anxiety and incite minority emerging adult males to use marijuana as an externalizing coping mechanism ( Hurd, Stoddard, & Zimmerman, 2012 ; Reboussin et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%